Direct Product of Finite Interval-Valued Intuitionistic Fuzzy Ideals in BF-Algebra - Ramesh, D; Satyanarayana, B; Srimannarayana, N (International Journal of Engineering and Technology, 2018)
The present paper gives direct product of finite interval-valued intuitionistic fuzzy ideals.  Furthermore, we add more useful results and also prove that, let be interval-valued intuitionistic fuzzy ideal of BF-algebra X. If  and for any, then  is an interval-valued intuitionistic fuzzy H-ideal of BF-algebra X.